2021
DOI: 10.3390/ani11051204
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of Quality Traits of Table Eggs and Eggshell Mineral Composition Depending on Hens’ Breed and Eggshell Color

Abstract: The aim of the study was to evaluate the relationship between the eggshell color parameters and its mineral composition as well as the internal quality of eggs derived from various breeds of hens, varied by eggshell color: seledine from Araucana, brown from Marans, and white from Leghorn. The sample consisted of 180 eggs (60/group) The eggshell color was measured using CIE L*a*b* system. The quality evaluation included traits of whole egg (weight, specific gravity, proportions of elements, shape index), yolk (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 33 publications
3
32
0
2
Order By: Relevance
“…This study detected 19 yolk free amino acids: aspartic acid (Y_Asp), glutamic acid (Y_Glu), asparagine (Y_Asn), serine (Y_Ser), glutamine (Y_Gln), glycine (Y_Gly), histidine (Y_His), arginine (Y_Arg), threonine (Y_Thr), alanine (Y_Ala), proline (Y_Pro), tyrosine (Y_Tyr), valine (Y_Val), methionine (Y_Met), cysteine (Y_Cys), isoleucine (Y_Ile), Leucine (Y_Leu), phenylalanine (Y_Phe), and lysine (Y_Lys). Tables 2 and S1 show 19…”
Section: Yolk Free Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study detected 19 yolk free amino acids: aspartic acid (Y_Asp), glutamic acid (Y_Glu), asparagine (Y_Asn), serine (Y_Ser), glutamine (Y_Gln), glycine (Y_Gly), histidine (Y_His), arginine (Y_Arg), threonine (Y_Thr), alanine (Y_Ala), proline (Y_Pro), tyrosine (Y_Tyr), valine (Y_Val), methionine (Y_Met), cysteine (Y_Cys), isoleucine (Y_Ile), Leucine (Y_Leu), phenylalanine (Y_Phe), and lysine (Y_Lys). Tables 2 and S1 show 19…”
Section: Yolk Free Amino Acidsmentioning
confidence: 99%
“…Therefore, eggs from several breeds may express a large variation in the appearance of eggs and contents of yolk and albumen caused by differences in genetic background. For example, the eggshell color of the Araucana that has South American origin is blue, which is significantly different from the white eggshell color of White Leghorn [18,19]. Also, it has been reported that the contents of fatty acids, cholesterol, protein, ash, and mineral in eggs [20][21][22] significantly differed among several breeds and strains.…”
Section: Introductionmentioning
confidence: 98%
“…The color of the eggshell (expressed as % whiteness) was lighter in eggs from 1-yr-old geese, and at the end of laying. The differences may concern the even distribution of the pigment in the eggshell and its intensity ( Drabik et al, 2021 ). This may indicate that less pigment is deposited in younger females and at the end of laying.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature studies, it has been reported that variation in egg color and origin leads to quality variability in egg composition [14]. Brown chicken eggs have been found to possess a heavier weight and higher levels of albumen and vitamin E than white eggs.…”
Section: Introductionmentioning
confidence: 99%
“…White eggs are lighter in weight and have higher levels of yolk, vitamin A, and total fat content (because of increased polyunsaturated and saturated fats in white eggs) than brown eggs [15]. The mineral composition and quality of eggshells have also varied according to egg color/origin, with brown eggshells having greater breaking strength and higher levels of calcium, magnesium, copper, aluminum, and zinc than white eggshells [14]. The effect of different egg colors/origins on quality as well as the activity of ESM has not been studied before.…”
Section: Introductionmentioning
confidence: 99%